New Therapeutic Horizon of Graves’ Hyperthyroidism: Treatment Regimens Based on Immunology and Ingredients From Traditional Chinese Medicine - He, Qiongyao; Dong, Hui; Gong, Minmin; Guo, Yujin; Xia, Qingsong; Gong, Jing; Lu, Fuer (Frontiers in Pharmacology, 2022)
Graves' disease is an autoimmune disease characterized by goiter and hyperthyroidism, and 25% patients develop GO. Traditional treatment options, such as antithyroid drugs, radioiodine or thyroidectomy, have remained largely unchanged over the past 70 years. For many patients, there is a high rate of recurrence after antithyroid drugs and lifelong hypothyroidism after ablation and thyroidectomy. The symptoms and quality of life of some patients have not been effectively improved. The clinical demand for new therapeutic regimens, coupled with a deeper understanding of the pathophysiology and immunobiology of Graves' disease, has led to the emergence of several new therapeutic ideas, including biologics, small molecule peptides, immunomodulators and teprotumumab, a specific antibody targeting IGF-1R. Besides, the elements of TCM have attracted more and more interests in modern medicine, because some effective components have been successfully used in the treatment of autoimmune diseases. Based on the pathophysiology and efficacy of clinical management and treatment in Graves’ hyperthyroidism, here we review the new strategies under investigation and summarize the effective components of traditional Chinese medicine used for Graves’ hyperthyroidism, and explore their mechanisms. These therapies have opened a new window for the treatment of Graves' disease, but the exact mechanism and the research direction still need to be further explored.